2021
DOI: 10.15294/jpii.v10i2.27509
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teachers' Comprehension and Readiness in Implementing STEM through Science Learning Simulation

Abstract: This study expects to discover the improvement of science teachers' comprehension of the STEM concept, the improvement of teachers' readiness in implementing it, and the relationship between the comprehension of STEM concepts and readiness in implementing it in learning science. The participants were 50 science teachers from a few junior high schools in Ciamis who joined the workshop and simulated natural science learning dependent on STEM concepts in the Galuh University in Ciamis, Indonesia. The method of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This is also evidence of the effectiveness of Stage 5, both on students and teachers. This is quite similar to the results reported by Toto et al (2021), where science teachers' understanding and rea-diness in implementing STEM were improved through implementing STEM in their teaching. Another implication is that teachers' knowledge and skill are vital to successfully organizing STEM activities because teachers "play a critical role in the success of new reforms," as Nugroho et al (2019), yet teacher STEM pedagogical content knowledge will be developed through real teaching experience.…”
Section: Figure 5 a Sample Tested Objectsupporting
confidence: 89%
“…This is also evidence of the effectiveness of Stage 5, both on students and teachers. This is quite similar to the results reported by Toto et al (2021), where science teachers' understanding and rea-diness in implementing STEM were improved through implementing STEM in their teaching. Another implication is that teachers' knowledge and skill are vital to successfully organizing STEM activities because teachers "play a critical role in the success of new reforms," as Nugroho et al (2019), yet teacher STEM pedagogical content knowledge will be developed through real teaching experience.…”
Section: Figure 5 a Sample Tested Objectsupporting
confidence: 89%
“…The STEM approach must involve the active participation of many parties, including students, teachers, administrators, and laboratory assistants (Altan & Ercan, 2016;Al Salami et al, 2017;Houchens et al, 2017;Suebsing & Nuangchalerm, 2021). STEM learning has the following characteristics: (1) focus on world issues and problems; (2) the engineering design process in learning; (3) involve students directly; (4) students are involved in productive work teams; (5) apply rigorous science and mathematics content in learning; (6) failure in practicum is an important lesson material to find the correct answer (Toto et al, 2021); (7) the ability to read and write science and think scientifically.…”
Section: Resultsmentioning
confidence: 99%
“…In Southeast Asian region, Saat et al (2021) 3 / 21 confidence and enthusiasm, and provided exchange information and support between schools and universities. In Indonesia, Toto et al (2021) reported increased teachers' understanding and readiness to implement STEM education after joining a science learning simulation PD workshop. Similarly, through a Thai-based PD program, Suebsing and Nuangchalerm (2021) reported increased teacher understanding and satisfaction toward STEM.…”
Section: Teacher and Pre-service Teacher On Stem Educationmentioning
confidence: 99%